Atypical cyclopia with ankylosed monster calf and its management through fetotomy- A case report - Yadav, Deepak; Yadav, Hanuman Prasad; Singh, Umed (Buffalo Bulletin, 2024)
A case of dystocia associated with malpresentation and atypical cyclopic monster with ankylosed limbs was delivered Per-vaginal with the help of fetotomy in a Murrah (Bubalus bubalis) buffalo.